2020
DOI: 10.1016/j.ijid.2020.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Management of a COVID-19 outbreak in a hotel in Tenerife, Spain

Abstract: Since the first accounts of SARS-CoV-2, authorities have encountered numerous unprecedented situations threatening public health. This rapid communication addresses events that led to the quarantining of a hotel in Tenerife, Spain and the effectiveness of the rapidly implemented control measures. In total, eight cases have been associated with the hotel. Due to the international nature of the guests, had these timely precautions not been in place, a multinational cluster might have formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Such a cluster of cases was reported in India where a group of 23 Italian tourists along with three Indians visited several tourist places, and the index case infected 16 tourists with an attack rate of 65.4% ( Vivian Thangaraj et al, 2020 ), which was higher than existing literature such as 5.7% in Shenzhen, China ( Bi et al, 2020 ). Another study also reported a cluster of eight cases infected in a hotel in Spain ( Hoefer et al, 2020 ). These studies illustrate the high risk of infections among tourists, and protection measures must be strictly implemented.…”
Section: Resultsmentioning
confidence: 91%
“…Such a cluster of cases was reported in India where a group of 23 Italian tourists along with three Indians visited several tourist places, and the index case infected 16 tourists with an attack rate of 65.4% ( Vivian Thangaraj et al, 2020 ), which was higher than existing literature such as 5.7% in Shenzhen, China ( Bi et al, 2020 ). Another study also reported a cluster of eight cases infected in a hotel in Spain ( Hoefer et al, 2020 ). These studies illustrate the high risk of infections among tourists, and protection measures must be strictly implemented.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, a worldwide event has been the economic crisis emerged in 2007, which affected the tourism industry ( Ritchie, Amaya Molinar, & Frechtling, 2010 ; Senbeto & Hon, 2020 ). More recently, the COVID-19 pandemic also has caused a severe impact on the tourism field in general, and on the hotel sector in particular (e.g., Gössling et al, 2020 ; Hoefer et al, 2020 ). In this context, hotel managers must be prepared not only to react when changes occur, but to anticipate them in order to meet challenges and maximise opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are limited studies in the literature, they are guiding for managing pandemic. Among these studies, Hoefer et al (2020) reported eight cases associated with managing a COVID-19 outbreak in a hotel in Tenerife, Spain. They highlighted that the collaboration and communication between the Public Health authorities and the hotel management were vital for controlling the COVID-19 pandemic.…”
Section: Literature Revie Wmentioning
confidence: 99%